2010
DOI: 10.1016/j.jnucmat.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Creep behaviour of as received, aged and cold worked INCONEL 617 at 850°C and 950°C

Abstract: a b s t r a c tThe effect of initial microstructure on alloy 617 creep behaviour has been investigated at 850°C and 950°C. The solution treated material shows non-classical creep behaviour at both temperatures with a strain rate drop at the beginning of the tests followed by a creep rate increase to a plateau before the onset of the tertiary creep. The intragranular secondary carbides which precipitate early at test temperature are responsible of the strong initial hardening effect by pinning the dislocations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…Hardness testing was also performed on the four crept samples and the average hardness is shown in Table 4. The high temperature exposure causes the as-received microstructure to evolve [9][10][11][12][16][17][18][19][20][21][22]. With the exception of µ phase, which only precipitates in the samples exposed at temperatures equal or higher than 700ºC, MX, M 23 C 6 , M 6 C and γ' are encountered in all the crept samples.…”
Section: Microstructural Analysis Of Alloy In617 Crept Specimensmentioning
confidence: 99%
“…Hardness testing was also performed on the four crept samples and the average hardness is shown in Table 4. The high temperature exposure causes the as-received microstructure to evolve [9][10][11][12][16][17][18][19][20][21][22]. With the exception of µ phase, which only precipitates in the samples exposed at temperatures equal or higher than 700ºC, MX, M 23 C 6 , M 6 C and γ' are encountered in all the crept samples.…”
Section: Microstructural Analysis Of Alloy In617 Crept Specimensmentioning
confidence: 99%
“…M. Akbari-Garakani et al [2] reported the formation of continuous network of M23C6 carbides along grain boundaries on exposed materials which facilitated grain boundary sliding easily and resulted in a decreased creep life compared to new materials. M. Cabibbo et al [3] also observed similar type of the M23C6 carbides along grain boundaries which contribute to the formation of film morphology. Then, grain boundary sliding occurred and caused creep rupture.…”
Section: Introductionmentioning
confidence: 76%
“…[1][2][3]. It is well-known that M23C6 carbide network is formed along grain boundaries during long-term exposure at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, most of creep tests in the previous papers were conducted at temperatures of 850 to 1000°C, which is much higher than the temperature conditions of A-USC. [18,19].…”
Section: Introductionmentioning
confidence: 99%